Social (Pragmatic) Communication Disorder: Another name for the Broad Autism Phenotype?. (November 2019) - Flax, Judy; Gwin, Christine; Wilson, Sherri; Fradkin, Yuli; Buyske, Steve; Brzustowicz, Linda
The Diagnostic and Statistical Manual of Mental Disorders ' (5th ed.) Social (Pragmatic) Communication Disorder is meant to capture the social elements of communication dysfunction in children who do not meet autism spectrum disorder criteria. It is unclear whether Social (Pragmatic) Communication Disorder captures these elements without overlapping with Autism Spectrum Disorder or the Diagnostic and Statistical Manual of Mental Disorders ' (5th ed.) Language Disorder. Standardized behavioral assessments administered during a family genetics study were used to evaluate the social communication impairment and the restricted interests and repetitive behaviors in persons with autism spectrum disorder, language impairment, or neither. Social communication impairment and restricted interests and repetitive behavior were significantly correlated in all family members regardless of affection status. Rates of social communication impairment and restricted interests and repetitive behavior were highest in individuals with autism spectrum disorder. One-third of family members with language impairment presented with at least mild/moderate levels of social communication impairment (36.6%) and restricted interests and repetitive behavior (43.3%). A subset of unaffected members also presented with mild/moderate levels of social communication impairment (parents = 10.1%, siblings 11.6%) and restricted interests and repetitive behavior (parents = 14.0%, siblings = 22.1%). The majority of child family members with mild/moderate levels of social communication impairment had similar restricted interest and repetitive behavior levels reflecting criteria representing the Broad Autism Phenotype. These data suggest that social pragmatic communication disorder does not capture the profiles of children who have both social communication impairment and restricted interests and repetitive behavior but are in need of clinical services.